1992
DOI: 10.1093/oxfordjournals.jbchem.a123723
|View full text |Cite
|
Sign up to set email alerts
|

Autolytic Transition of μCalpain upon Activation as Resolved by Antibodies Distinguishing between the Pre- and Post-Autolysis Forms1

Abstract: A novel method to observe the autolytic activation of a mammalian cytoplasmic calcium protease, mu-calpain, was developed using a set of antipeptidic antibodies capable of distinguishing between the pre- and post-autolysis forms of the enzyme. Antibodies raised against synthetic peptides designed to match the N-terminal sequences of the pre- and post-autolysis forms of the mu-calpain large subunit reacted specifically with the corresponding form of calpain and not with the other. The antibodies were specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 0 publications
2
113
0
Order By: Relevance
“…Croall et al [18] have raised antibodies specific for unautolysed m-and pcalpain. Saido et al [19] have raised antibodies against unautolysed and autolysed forms ofp-calpain. The data in this paper should facilitate experiments using the antibody approach to investigate in vivo activation of m-calpain.…”
Section: Discussionmentioning
confidence: 99%
“…Croall et al [18] have raised antibodies specific for unautolysed m-and pcalpain. Saido et al [19] have raised antibodies against unautolysed and autolysed forms ofp-calpain. The data in this paper should facilitate experiments using the antibody approach to investigate in vivo activation of m-calpain.…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal antibodies were obtained against β3 integrin (Chemicon); against HA epitope (Santa Cruz Biotechnology); against bovine non-erythroid spectrin (P14), a gift from Aleksander Sikorski (University of Wroclaw, Poland); against calpain-induced β3 integrin fragment (Ab754), a gift from Xiaoping Du (College of Medicine, Chicago, Illinois). Polyclonal antibodies against autolysed form of µ-calpain and polyclonal antibodies against calpain-induced 150 kD fragment of spectrin were described previously (Saido et al, 1992;Saido et al, 1993), TRITC (tetramethyl rhodamine isothiocyanate)-conjugated phalloidin was from Sigma.…”
Section: Reagentsmentioning
confidence: 99%
“…Previous studies in human platelets have demonstrated calcium-dependent autoproteolytic conversion of the 80-kDa subunit of calpain to its 76-kDa active form (3). The antibodies used in these studies have been raised against synthetic peptides corresponding to the N-terminal sequence of the large subunit of both forms of calpain (28). Immunoblot analysis of whole cell lysates with these antibodies represents a sensitive, specific, and direct means of monitoring calpain activation within the cell (29).…”
Section: Fig 2 Effect Of Calpain Activation On the Cytoskeletal Assmentioning
confidence: 99%